AIDS-related opportunistic illnesses and early initiation of HIV care remain critical in the contemporary HAART era: a retrospective cohort study in Taiwan - Lee, Chun-Yuan (BMC Infect Dis, 2018)
BACKGROUND: No study has reported the epidemiology of AIDS-related opportunistic illnesses (AOIs) in patients with newly diagnosed HIV infection in Taiwan in the past decade. Understanding the current trends in AOI-related morbidity/mortality is essential in improving patient care and optimizing current public health strategies to further reduce AOIs in Taiwan in the era of contemporary highly active antiretroviral therapy (HAART). METHODS: Eligible patients were evaluated at two referral centers between 2010 and 2015. The patients were stratified by date of diagnosis into three periods: 2010–2011, 2012–2013, and 2014–2015. The demographics, HIV stage at presentation according to the United States CDC 2014 case definition, laboratory variables, and the occurrence of AOIs and associated outcomes were compared among the patients. Logistic regression and Cox regression were respectively used to identify variables associated with the occurrence of AOIs within 90 days of HIV enrollment and all-cause mortality. RESULTS: Over a mean observation period of 469 days, 1264 patients with newly diagnosed HIV with a mean age of 29 years and mean CD4 count of 275 cells/μL experienced 394 AOI episodes in 290 events. At presentation, 37.7% of the patients had AIDS; the frequency did not significantly differ across groups. The overall proportion of AOIs within the study period was 21.0%, and no decline across groups was observed. The majority of AOIs (91.7%) developed within 90 days of enrollment. All-cause and AOI-related mortality did not significantly differ across groups. Throughout the three study periods, AOIs remained the main cause of death (47/56, 83.9%), especially within 180 days of enrollment (40/42, 95.2%). A CD4 cell count of < 200 cells/μL at presentation was associated with increased adjusted odds of an AOI within 90 days [adjusted odds ratio, 40.84; 95% confidence intervals (CI), 12.59–132.49] and an elevated adjusted hazard of all-cause mortality (adjusted hazard ratio, 11.03; 95% CI, 1.51–80.64). CONCLUSIONS: Despite efforts toward HIV prevention and management, early HIV care in Taiwan continues to be critically affected by AOI-related morbidity and mortality in the era of contemporary HAART. Additional targeted interventions are required for the earlier diagnosis of patients with HIV. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12879-018-3251-1) contains supplementary material, which is available to authorized users.